Animal Welfare Control—Inspection Findings and the Threshold for Requesting a Police Investigation - Valtonen, Elli; Koskela, Tarja; Valros, Anna; Hänninen, Laura (Frontiers in Veterinary Science, 2021)
An increasing proportion of animal welfare violations in Finland are related to companion animals. However, only a small number of these issues are investigated or prosecuted. The aims of this study were (i) to describe the inspection findings and the resulting actions of the official municipal veterinarians in the Finnish Capital Region and (ii) to identify the factors that predict their submissions of investigation requests to the police. Our data consisted of animal welfare complaints and official veterinarians’ inspection reports and decisions from 811 cases of animal welfare control in the Finnish Capital Region. The data covered the period from March 2019 to April 2020. We performed logistic regression analyses to identify the factors that best predict when official veterinarians detect non-compliances and cases are reported for police investigation. In 86% (696/811) of the cases, the veterinarians performed at least one animal welfare inspection, and/or received information from the police, or otherwise investigated the complaint. The most common forms of non-compliance were lack of basic maintenance and care (42%, 295/696) and insufficient veterinary care (27%, 185/696). The veterinarians requested for a police investigation in 9.6% (44/460) of all cases with detected non-compliances. The best predictors for detecting non-compliances with the animal welfare legislation were complaints of insufficient veterinary care (OR 1.9, CI 1.1-3.4), the cases assessed by the information from the police and/or an animal shelter (OR 15.2, CI 7.9-29.2), at least one inspection in an animal’s premises with prior warning (OR 11.2, CI 5.5-22.6), and without prior warning (OR 17.0, CI 9.7-29.5). Complaints of violence against animals were negatively associated with detecting non-compliances (OR 0.5, CI 0.3-0.9). However, the detection of violence against animals predicted requests for police investigations (OR 9.3, CI 3.1-27.9), as did the execution of permanent urgent measures by official veterinarians (OR 4.9, CI 1.9-12.9). To improve the animal welfare control system and the investigation of crimes against animals, cooperation between officials should be developed. Further studies are needed to improve the understanding of the prevalence of violence against animals, and to advance methods used by animal welfare control to identify cases of violence.